TURISMO COMUNITÁRIO E POPULAÇÕES TRADICIONAIS: O CASO DO FAXINAL BARRA BONITA NO MUNICÍPIO DE PRUDENTÓPOLIS - PR - Lemes, Pedro Henrique Sanches (2009)
In the early 1980 the alternative tourism begins to gain strength in Brazilian market. This activity shows problems caused by mass tourism that explore fragile environment in an unthinking way putting the customs and habits of the local communities under threat as well as the local flora and fauna. In Paraná State there is a great potential to develop this kind of tourism activity in traditional communities. These communities are named faxinais, where is developed a community production with a joint area to raise animals in an environment of Araucária Forest and private areas to plant. Nowadays there are about 44 faxinal areas in Center –South of the State, 07 of them are located in Prudentópolis. For this reason the purpose of this research is to evaluate the touristic potential in faxinal communities of this borough. There are already areas around the faxinais exploring ecological tourism (visit to the waterfalls) and also the adventure tourism (rapel, trekking). Through Community Tourism, a tourist segmentation that fits in the alternative tourism and above all prioritizes the local community well-being, respecting their limits and desires and allowing that local people carry out the tourism management. So the intention of this study is the inclusion of the faxinal areas in this system. For this two complex of touristic narratives have been identified: ethnic(typical food, costumes, traditions, songs, dance, religion, everyday work) and the economic and technological history( subsistence agriculture, wood and erva-mate extraction, tropeirismo, pig rising and tobacco agribusiness). It is believed that this segmentation can mean an economical improvement for these communities and also the preservation of their cultural environment.